PEMETAAN AUDIENS IKLAN ROKOK GUDANG GARAM FILTER INTERNASIONAL (VERSI PRIA PUNYA SELERA) 2023 DALAM KONSEP RESEPSI STUART HALL - Maulida, Amilia Krisda; Kamajaya, Gede; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This research aims to map how audiences understand the Gudang Garam Filter International cigarette advertisement with the theme "Men Have Taste" released in 2023. This study uses Stuart Hall's perception theory to see how people understand the message in the advertisement, by dividing audiences into three groups: 1) those who fully accept the message (dominant hegemonic), 2) those who accept part and dominate certain parts (negotiated), and 3) those who reject the message in the advertisement as a whole (opposition). Using a qualitative approach, this research analyzes how people interpret the advertisement. The results show that audiences have different points of view. The dominant audience accepts the advertisement message as a whole and considers the representation of masculinity in the advertisement as correct. The negotiated audience agrees with some parts but criticizes the gender stereotypes in the advertisement. The oppositional audience rejects the message in the advertisement because they consider the advertisement irrelevant to gender and health issues. This research shows how a person's point of view in understanding advertisements is influenced by cultural, social, and individual values, leading to a deeper understanding of how advertisements are received and interpreted by various audience groups. Keywords: Advertisement, Cigarettes, Masculinity